(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
We present new and validated names of some syntaxa of the vegetation class Festuco-Brometea. True steppe vegetation of Eastern Europe, which is distributed from the Eastern part of Romania to the Urals, we propose to consider as a separate order Galatello villosae-Stipetalia lessingianae. It is an intermediate link between meso-xeric communities of the Central and Eastern Europe of the order Festucetalia valesiacae Soo 1947 from one hand, and desert steppe vegetation of the order Tanaceto achilleifolii-Stipetalia lessingianae Lysenko et Mucina in Mucina et al. 2016 from the other hand. We describe a new order Cephalario uralensis-Jurineetalia stoechadifolii for rocky dwarf-shrub calcareous grasslands of the Pontic region. It replaces the order Stipo pulcherrimae-Festucetalia pallentis Pop 1968 in Eastern Europe due to more continental conditions. We validate the name of the alliance Galio campanulati-Poion versicoloris, as well as its type association. This alliance includes rocky grasslands on limestone outcrops from the Central and Western Podillia and belongs to the order Stipo pulcherrimae-Festucetalia pallentis Pop 1968 on the easternmost range of its distribution. We describe a new association of the desert steppes from the Republic of Kalmykia of the alliance Tanaceto achilleifolii-Stipion lessingianae. In addition, we publish the replacement name Paeonio tenuifolii-Stipetum tirsae as a substitute for illegitimate later homonym.